Differential virological and immunological outcome of severe acute respiratory syndrome coronavirus infection in susceptible and resistant transgenic mice expressing human angiotensin-converting enzyme 2 - Yoshikawa, Naoko; Yoshikawa, Tomoki; Hill, Terence; Huang, Cheng; Watts, Douglas M; Makino, Shinji; Milligan, Gregg; Chan, Tehsheng; Peters, Clarence J; Tseng, Chien-Te K (Journal of virology, 2009)
We previously reported that transgenic (Tg) mice expressing human angiotensin-converting enzyme 2 (hACE2), the receptor for severe acute respiratory syndrome coronavirus (SARS-CoV), were highly susceptible to SARS-CoV infection, which resulted in the development of disease of various severity and even death in some lineages. In this study, we further characterized and compared the pathogeneses of SARS-CoV infection in two of the most stable Tg lineages, AC70 and AC22, representing those susceptible and resistant to the lethal SARS-CoV infection, respectively. The kinetics of virus replication and the inflammatory responses within the lungs and brains, as well as the clinical and pathological outcomes, were assessed in each lineage. In addition, we generated information on lymphocyte subsets and mitogen-mediated proliferation of splenocytes. We found that while both lineages were permissive to SARS-CoV infection, causing elevated secretion of many inflammatory mediators within the lungs and brains, viral infection appeared to be more intense in AC70 than in AC22 mice, especially in the brain. Moreover, such infection was accompanied by a more profound immune suppression in the former, as evidenced by the extensive loss of T cells, compromised responses to concanavalin A stimulation, and absence of inflammatory infiltrates within the brain. We also found that CD8(+) T cells were partially effective in attenuating the pathogenesis of SARS-CoV infection in lethality-resistant AC22 mice. Collectively, our data revealed a more intense viral infection and immunosuppression in AC70 mice than in AC22 mice, thereby providing us with an immunopathogenic basis for the fatal outcome of SARS-CoV infection in the AC70 mice.